How to predict the culprit segment in percutaneous transforaminal endoscopic surgery under local anesthesia for surgical treatment of lumbar degenerative diseases? Radiologic images or clinical symptoms - Zhou, Tianyao; Ma, Tianle; Gu, Yutong; Zhang, Liang; Che, Wu; Wang, Yichao (Frontiers in Surgery, 2023)
Objective: Percutaneous transforaminal endoscopic surgery (PTES) is a novel minimally invasive technique that has been used in the treatment of lumbar degenerative diseases (LDDs). PTES under local anesthesia was performed to treat the culprit segment of LDDs predicted by radiologic images or clinical symptoms, and the efficacy, security and feasibility were evaluated. Methods: 87 cases of LDDs with nerve root symptoms, which were not consistent with lumbar degenerative levels and degree on MRI and CT, were treated with PTES under local anesthesia in day surgery ward from Jan 2015 to Dec 2019. 42 patients, whose culprit segment was predicted by radiologic images are included in group A. The other 45 patients, whose culprit segment was predicted by clinical symptoms are included in group B. Leg pain VAS and ODI before and after PTES are recorded. The outcome is defined according to MacNab grade at 2-year follow-up. Postoperative complications are recorded. Results: In group A, 2 patients underwent PTES for 1 segment, 37 patients for 2 segments and 3 patients for 3 segments. One of 1-segment PTES had no relief of symptoms and underwent another PTES for other culprit segment 3 months after surgery. In group B 44 of 45 patients were treated using PTES for 1 segment and 1 patient for 2 segments. Group B showed significantly less operative duration, less blood loss and less fluoroscopy frequency than group A (P<0.001). VAS score of leg pain and ODI significantly dropped after operation in both groups (P<0.001), and the excellent and good rate was 97.6% (41/42) in group A and 100% (45/45) in group B at 2-year follow-up. The leg pain VAS of group B was significantly lower than that of group A immediately, 1 week, 1 month, 2 months and 3 months after surgery (P<0.001). There was no statistical difference in ODI, and the excellent and good rate between two groups. No complications such as wound infection, permanent nerve injury were observed. Conclusion: It is much more accurate to predict the culprit segment according to clinical symptoms than radiologic images in PTES under local anesthesia for surgical treatment of LDDs.